Surface Modification Improves Spinel LiCoO2 Li-Ion Battery Cathode Materials Grown by Low Temperature Solvothermal Flow Reaction - Nicolosi, Valeria (My University, 2024)
Methods that provide routes to LiCoO2 growth with lower energy requirements from recycled battery cathode ashes are important for sustainable Li-ion battery technology . Here, a low temperature route to a stable, coated spinel-phase LT-LCO material with secondary Co3O4 phase can be achieved at 300 °C directly from the layered double hydroxide [Li2(ox)2][Co5(OH)8] product of solvothermally synthesized LiOH and CoCl2. The low-temperature LiCoO2 materials (known as LT-LCO) consist of spinel-phase LCO and secondary Co3O4 phase. As a cathode in lithium batteries, we used a solution-based method of coating with an ionic conductor LiAlO2 with AlF3 to mitigate sluggish reversible lithiation kinetics and the poor cycling and rate performance of as-synthesized spinel LT-LCO. The coating modification promotes reversible lithium ion transfer and stabilizes the spinel structure. The modified LT-LCO cathode has significantly better overall capacity and rate performance, with a capacity retention of ∼80 mAh g−1 after 150 cycles (factoring the LT-LCO and Co3O4 mass). The initial first cycle coulombic efficiency significantly improves to >95%. The data show that even spinel phase LCO grown by this solvothermal route cycles stably with a useful specific capacity and rate response in the voltage range 2.0-4.2 V.
Keywords: LiCoO2 growth; coated spinel-phase LT-LCO materiAL; solvothermal route cycles; LiCoO2 growth; coated spinel-phase LT-LCO materiAL; solvothermal route cycles